1990
DOI: 10.1111/j.1464-5491.1990.tb01348.x
|View full text |Cite
|
Sign up to set email alerts
|

A Project in Diabetes Education for Children

Abstract: Forty-eight families with children less than 13 years old attending a paediatric diabetic clinic volunteered for a 2-year randomized crossover trial to determine whether an informal education programme (diabetic club) could improve diabetic control. Group A attended the diabetic club for 10 afternoons of informal education in the first year, while Group B continued at the routine clinic (5 visits per year). For the second year Group A returned to the clinic, Group B attended the club. Glycosylated haemoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 15 publications
0
52
0
1
Order By: Relevance
“…Many have also noted the lack of a relationship between SMBG and glycemic control for combined I-1 and I-2 C: Relaxation training to cope with stress All groups got nine weekly sessions of 1.5 h BL, baseline; BS, blood sugar; BP, blood pressure; C, C-1, C-2, control groups; CAI, computer-assisted instruction; CHO, carbohydrate; D/SBP, diastolic/systolic blood pressure; DM, diabetes mellitus; DM2, type 2 diabetes; FBS, fasting blood sugar; F/U, follow-up; HCW, health-care worker; I, I-1, I-2, I-3, intervention groups; IP, inpatient; NSD, no significant difference; OP, outpatient; PA, physical activity; q, every; RN, registered nurse; SD, significant difference; TC, telephone call. subjects with type 2 diabetes (111-116), although several randomized controlled trials have shown a relationship in type 1 diabetes (117,118).…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
“…Many have also noted the lack of a relationship between SMBG and glycemic control for combined I-1 and I-2 C: Relaxation training to cope with stress All groups got nine weekly sessions of 1.5 h BL, baseline; BS, blood sugar; BP, blood pressure; C, C-1, C-2, control groups; CAI, computer-assisted instruction; CHO, carbohydrate; D/SBP, diastolic/systolic blood pressure; DM, diabetes mellitus; DM2, type 2 diabetes; FBS, fasting blood sugar; F/U, follow-up; HCW, health-care worker; I, I-1, I-2, I-3, intervention groups; IP, inpatient; NSD, no significant difference; OP, outpatient; PA, physical activity; q, every; RN, registered nurse; SD, significant difference; TC, telephone call. subjects with type 2 diabetes (111-116), although several randomized controlled trials have shown a relationship in type 1 diabetes (117,118).…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
“…14,28,30,38 The number of sessions ranged from 1 19,20 to 19 18 and the duration of the sessions ranged from 10 minutes 18 to 3.5 hours. 15 All trials except one provided a form of usual care to the control group. The one exception provided an attention control condition with an entertainment video game.…”
Section: Resultsmentioning
confidence: 99%
“…The one exception provided an attention control condition with an entertainment video game. 16 Three computerized approaches were observed in these trials: computerized touch-screen assessment and instruction, 15 Trials included in the games or simulation category represent an educational video game with role playing, 16 a simulation for hypoglycemia problem solving, 30 and an interactive educational diabetes simulator that could be downloaded from the Internet. 33 There were 24 diabetes education topics included in the trials ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations